Construction of identities in oral narratives in the potions Quilombo – MG - Peixoto, Ana Cristina Santos; Alves, Diocles Igor Castro Pires (Seven Editora, 2023)
This article describes the discourses of the quilombola peoples, understood as traditional communities. We reveal the constitution of identities of the quilombolas of the Potions Territory in Minas Gerais. This investigation is anchored in the analysis of the French line of discourse and in anthropological studies. We used oral narratives from interviews, selected the fragments that most interested for this article and proceeded to qualitative analysis from the discourse analysis. The historical processes that constitute them also identify them and claim other identities. It was found that the struggle of the black people takes place in the social movements in a minimally organized way, the search for recognition and the dream of freedom have become essential instruments for their survival. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-121